2020
DOI: 10.3390/su12198208
|View full text |Cite
|
Sign up to set email alerts
|

The Dependence of Cocksfoot Productivity of Liming and Nitrogen Application and the Assessment of Qualitative Parameters and Environmental Impact Using Biomass for Biofuels

Abstract: In order to evaluate the liming and nitrogen efficiency of cocksfoot (Dactylisglomerata L.) productivity, a field experiment was performed in Western Lithuania’s naturally acidic Retisol area (55°43′ N, 21°27′ E). Based on seven years of research data, dry mass (DM) yield (including first and second cuttings) reliably varied depending on the growing year, from 4.57 to 7.34 t ha−1. The most significant and positive impact on DM yield was obtained by the application of higher liming (6.0 t ha−1 CaCO3) and nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…When adequately fertilized, they have high yield potential for dry matter, protein and carbohydrates. Cocksfoot is one of the most important fodder crops in Europe and in the world [36,37]. It attains high yields and is disease-resistant [36], as well as highly resistant to drought [38].…”
Section: Introductionmentioning
confidence: 99%
“…When adequately fertilized, they have high yield potential for dry matter, protein and carbohydrates. Cocksfoot is one of the most important fodder crops in Europe and in the world [36,37]. It attains high yields and is disease-resistant [36], as well as highly resistant to drought [38].…”
Section: Introductionmentioning
confidence: 99%
“…The literature reports that cocksfoot grows well in drought conditions [8] and under water stress [9]. Research conducted on acidic soils of Lithuania showed that the highest yield of cocksfoot was obtained with high nitrogen fertilization with simultaneous liming [10]. In turn, perennial ryegrass is sensitive to high soil moisture and drought stress [11].…”
Section: Introductionmentioning
confidence: 99%
“…It can be mowed or grazed and sown in mixtures with clovers or alfalfa [44]. Cocksfoot contains a lot of fiber; therefore, its nutritional value is sometimes lower than that of other grasses [45]. It is a commonly cultivated grass in Europe.…”
Section: Introductionmentioning
confidence: 99%